Lycopene Pretreatment Ameliorates Acute Ethanol Induced NAD+ Depletion in Human Astroglial Cells. (14th May 2015) - Guest, Jade; Guillemin, Gilles J.; Heng, Benjamin; Grant, Ross
Abstract : Excessive alcohol consumption is associated with reduced brain volume and cognition. While the mechanisms by which ethanol induces these deleterious effects in vivo are varied most are associated with increased inflammatory and oxidative processes. In order to further characterise the effect of acute ethanol exposure on oxidative damage and NAD + levels in the brain, human U251 astroglioma cells were exposed to physiologically relevant doses of ethanol (11 mM, 22 mM, 65 mM, and 100 mM) for ≤ 30 minutes. Ethanol exposure resulted in a dose dependent increase in both ROS and poly(ADP-ribose) polymer production. Significant decreases in total NAD(H) and sirtuin 1 activity were also observed at concentrations ≥ 22 mM. Similar to U251 cells, exposure to ethanol (≥22 mM) decreased levels of NAD(H) in primary human astrocytes. NAD(H) depletion in primary astrocytes was prevented by pretreatment with 1  μ M of lycopene for 3.5 hours. Unexpectedly, in U251 cells lycopene treatment at concentrations ≥ 5  μ M resulted in significant reductions in [NAD(H)]. This study suggests that exposure of the brain to alcohol at commonly observed blood concentrations may cause transitory oxidative damage which may be at least partly ameliorated by lycopene.